L’influence des Églises sur le processus de dévolution en Écosse - Edwige Camp (Revue LISA)
The two main Christian Churches in Scotland, the Presbyterian Church and the Catholic Church, each sent representatives to the Constitutional Convention which produced the recommendations serving as the basis for the devolved institutions set up in 1999 (Parliament and Executive). Since then, the Scottish Churches have been acting as pressure groups on the new institutions. This article deals with their involvement both in the devolution process and in the post-devolution period.